REAKSI PASAR BERUPA VOLUME PERDAGANGAN SAHAM SAAT STOCK SPLIT PADA PERUASAHAAN BEI TAHUN 2011-2013 - Merkusiwati, Ni Ketut Lely Aryani (E-Jurnal Akuntansi; Vol 9 No 1 (2014), 2014)
The market reaction is a signal given by investors on stock prices of companies in the capital market. This study aims to examine the information content of an event that announced the company. The research was conducted on all the companies listed in Indonesia Stock Exchange 2011-2013 is the stock-split. The number of samples taken 30 companies. Based on the test results of the analysis using paired smple t-test showed that there are differences ATVA, a decrease in the activity of the average trading volume before and after the stock split. This suggests that investors are less able to react to the announcement of a stock split that led to the decline over the ATVA company after the stock split. The decrease is caused because investors do not see a stock split as a beneficial information in the Indonesian economy experienced inflation and rising fuel prices.
Keywords: Market Reaction And Stock Trading Volume Activity